Working in cold environment and risk of developing rheumatoid arthritis: results from the Swedish EIRA case–control study. Issue 2 (16th August 2017) - Zeng, Pingling; Bengtsson, Camilla; Klareskog, Lars; Alfredsson, Lars
Abstract : Objectives: To investigate (1) whether working in cold environment (WCE) is associated with an increased risk of developing rheumatoid arthritis (RA) (overall), anticitrullinated protein antibody (ACPA)-positive RA and ACPA-negative RA and (2) whether WCE interacts with occupational physical workload in conferring RA risk. Methods: Data from the Swedish population-based case-control study Epidemiological Investigation of Rheumatoid Arthritis involving 3659 incident cases and 5925 controls were analysed. Study participants were asked whether they had ever worked in cold/outdoor environment along with their exposure duration and frequency. Occurrence of RA among exposed and unexposed subjects were compared by calculating ORs with 95% CI using logistic regression. Additive interactions between WCE and six types of physical workload were assessed using the principle of departure from additivity by calculating attributable proportion due to interaction (AP). Results: The OR associated with having ever worked in cold environment was 1.5 (95% CI 1.4 to 1.7) for RA (overall), 1.6 (95% CI 1.4 to 1.8) for ACPA-positive RA and 1.4 (95% CI 1.2 to 1.6) for ACPA-negative RA. The risk of developing RA increased with increasing cumulative dose of working in cold indoor environment (p value <0.001), but not working in cold outdoor environment. Positive additive interaction was observed between WCE and repetitive hand/finger movements (AP 0.3 (95% CI 0.1 to 0.5)). Conclusions: WCE is associated with increased risk of developing both ACPA-positive and ACPA-negative RA. A dose–response relationship was found between working in cold indoor environment and risk of developing RA. Moderate additive interaction was observed between exposure to cold environment and exposure to repetitive hand/finger movements.